Enzymatic hydrolysis ability and mechanical strength of cellulose fibres - Nazarov K.K., Qudratxudjayev M.A., Shukurxonova M.G (International Journal of Advanced Science and Technology, 2020)
The correlation between the mechanical strength and the enzymatic hydrolysis of cotton fibers wasstudied. In the course of research, it was proved that not strong, defective fibers (not suitable forindustry) are more exposed to enzymes. Moreover, the stronger the fiber, the higher its technologicalproperties, the higher the resistance of the fiber to biodegradation. It was also found that the fibers ofdiseased cotton plants are hydrolyzed at the highest rate compared to fibers of healthy plants.Moreover, the efficiency of enzymatic hydrolysis for some studied fiber samples can reach up to 77%in the yield of sugar substances. In addition, for the first time it was established that enzymatichydrolysis is a characteristic feature of the strength of cotton fiber, which allows us to develop newbiological criteria for assessing the strength of fiber in industry.